PENGARUH PERBEDAAN SUHU ANTAR RAK BEDENGAN TERHADAP HASIL PRODUKSI DAN PENDAPATAN USAHATANI JAMUR MERANG (Volvariella volvaceae) DENGAN MEDIA KAPAS - Fitri Hoerunnisa (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2018)
The purpose of this research are to analyze the effect of temperature’s difference on every rack to the weight of straw mushroom that will be produced and also to analyze the acceptance and income that will be earned by the mushroom’s farmer. The type of this research is quantitative research. The research is conduct at Kademangan Mushroom Farm, Setu, South Tangerang City. The selection of research sites is done purposively with the consideration that the selected location is the center of mushroom production in South Tangerang City. This study is conducted in March 2018 until April 2018. The sample that will be used in this research is thirty racks of shelf that filled with straw mushroom. Analysis of data used in this research is simple linear regression analysis, income analysis and RC Ratio. According to the research on the field, the best temperature for straw mushroom’s growth is ranged between 32,50C to 350C and the maximum production of straw mushroom is earned from shelf number 3 that located in the middle of the rack with 182 kg weight in one period of production. According to the analysis using simple linear regression analysis, the difference of temperatures between each rack has a significant effect to mushroom’s growth. And according to the acceptance and income analysis, the maximum income that is earned by shelf number 3 is Rp. 6.370.000 in one periode of production. The maximum income that is earned by the mushroom’s farmer is Rp. 17.535.000 and the total income that will be earned is Rp. 2698.014,00 with the value of the RC Ratio is 1,18 shows that straw mushroom cultivation business is efficient because RC Ratio value is more than one.